2021
DOI: 10.2196/27926
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Intention to Adopt mHealth Apps Among Dementia Caregivers With a Chronic Condition: Cross-sectional, Correlational Study

Abstract: Background In the United States, nearly 80% of family caregivers of people with dementia have at least one chronic condition. Dementia caregivers experience high stress and burden that adversely affect their health and self-management. mHealth apps can improve health and self-management among dementia caregivers with a chronic condition. However, mHealth app adoption by dementia caregivers is low, and reasons for this are not well understood. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…For example, recent research found that when care partners search for information and cannot meet the information need at that time, they often abandon the information behavior [ 18 ]. Furthermore, low-quality information is likely to reduce perceived usefulness, which has been shown to be a key factor influencing caregivers’ intention to adopt mobile health apps [ 56 ]. Lower scores on information are also concerning, as this score reflects that apps are often not tested for effectiveness in improving people living with ADRD or care partner outcomes, reducing the ability to safeguard against products that may not deliver on their advertised potential.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent research found that when care partners search for information and cannot meet the information need at that time, they often abandon the information behavior [ 18 ]. Furthermore, low-quality information is likely to reduce perceived usefulness, which has been shown to be a key factor influencing caregivers’ intention to adopt mobile health apps [ 56 ]. Lower scores on information are also concerning, as this score reflects that apps are often not tested for effectiveness in improving people living with ADRD or care partner outcomes, reducing the ability to safeguard against products that may not deliver on their advertised potential.…”
Section: Discussionmentioning
confidence: 99%
“…A study was done by Tulek et al, 2020 on caregiver burden, quality of life, and related factors in family caregivers of dementia patients in Turkey found that about 60% of the studied caregivers suffer from chronic illness (49) . Also, another study was done by Mendez et al, (2021) reported that about 47% of the caregivers of patients with dementia suffer from hypertension and about 20% have diabetes mellitus (34) .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Tulek et al, 2020 on burden, quality of life, and related factors in family caregivers of dementia patients in Turkey found that approximately 60% of the studied caregivers suffered from chronic illness [ 52 ]. Additionally, another study performed by Mendez et al (2021) reported that approximately 47% of the caregivers of patients with dementia suffer from hypertension and approximately 20% have diabetes mellitus [ 53 ].…”
Section: Discussionmentioning
confidence: 99%